The Organisation For Economic Cooperation And Development Guidelines Dan Pengaruhnya Terhadap Pengaturan Pajak Pertambahan Nilai Atas Jasa Di Indonesia - Fadhilatul Hikmah (Fakultas Hukum Universitas Islam Indonesia, 2020)
Research on the practice of collecting Value Added Tax (VAT/PPN) on service exports carried out in Indonesia uses two conflicting principles, namely the destination principle and the origin principle. The application of these two principles can eliminate the essence of VAT neutrality and lead to double taxation and unintended double taxation. According to the OECD, the most appropriate principle to apply in VAT collection is the destination principle. This normative research was conducted in order to obtain answers regarding the influence of the OECD Guidelines on International VAT/GST on VAT regulation on service exports in Indonesia. The results of the study conclude that although the OECD Guidelines on International VAT/GST is a type of soft law that is not binding on Indonesia, indirectly, by declaring itself to implement the BEPS action plan comprehensively, the government has voluntarily demonstrated its commitment to implementing the OECD guidelines which relating to VAT, including the International VAT/GST Guidelines. In other words, the destination principle is the only principle that should be used in collecting VAT on service exports in Indonesia.